Oral competence following facial nerve paralysis: Functional and quality of life measures. (4th March 2021) - Charters, Emma; Coulson, Susan
Abstract: Purpose: Oral competence refers to the maintenance of lip closure with sufficient strength to prevent anterior spillage of saliva, food and fluid, and to clearly articulate labial sounds. Despite facial nerve paralysis having an impact on eating, drinking and communicating, little research has been done in this area. Method: Studies examining oral competence associated with a diagnosis of facial nerve paralysis were considered using Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) statement checklists and evaluated for their risk of bias using the RevMan Risk of Bias Tool. Result: 44 articles were examined. There was an over-representation of case-series and cohort studies. All studies carried a high risk of bias due to lack of (a) validated outcome measures, (b) comparison group and (c) blinding or randomised assessors and participants. Studies primarily examined facial nerve intervention for the purpose of restoring smiling or facial aesthetics rather than oral competence. Conclusion: Whilst oral competence is often compromised after a facial nerve paralysis, it is inconsistently measured, managed and described. Further studies are required to examine the (a) incidence, (b) severity and (c) impact on quality of life relating to oral incompetence using validated measures at consistent time intervals.